A autocorreção como preservação da face do falante culto do Projeto NURC/SP - Santos, Marina Aparecida dos (2007)
This study demonstrates how educated speakers of NURC Project always maintain their face by using the self-correction. This academic work is grounded on the Analysis of Conversation theories and focuses Correction and Face Protection System which highlights the linguistic politeness. The face protection, which is characterized by clearness, hesitation, grammatical correction and repetition emphasizing the argument, was examined in 42 (forty two) examples that were selected in the inquiries of NURC Project. Part of the history of the Project is described as well as Goffman and Brown and Levinson s theories, with the purpose to clarify the contents of these and other studies that have been developed in academic area, regarding to this issue. Supported by these theories, a quantitative analysis of data collection in the 42 selected inquiries was done. The conclusion is that the educated speaker seems to be more worried with this linguistic performance in society. Thus, the speaker usually protects his face, especially when uses the self-correction